Fatal food anaphylaxis in adults and children - Elio Novembre; Mariannita Gelsomino; Lucia Liotti; Simona Barni; Francesca Mori; Mattia Giovannini; Carla Mastrorilli; Luca Pecoraro; Francesca Saretta; Riccardo Castagnoli; Stefania Arasi; Lucia Caminiti; et al. (Italian Journal of Pediatrics, 2024)
Abstract Anaphylaxis is a life-threatening reaction characterized by the acute onset of symptoms involving different organ systems and requiring immediate medical intervention. The incidence of fatal food anaphylaxis is 0.03 to 0.3 million/people/year. Most fatal food-induced anaphylaxis occurs in the second and third decades of life. The identified risk factors include the delayed use of epinephrine, the presence of asthma, the use of recreational drugs (alcohol, nicotine, cannabis, etc.), and an upright position. In the United Kingdom (UK) and Canada, the reported leading causal foods are peanuts and tree nuts. In Italy, milk seems to be the most common cause of fatal anaphylaxis in children < 18 years. Fatal food anaphylaxis in Italian children and adolescents almost always occurs outside and is characterized by cardiorespiratory arrest; auto-injectable adrenaline intramuscular was available in few cases. Mortality from food anaphylaxis, especially in children, is a very rare event with stable incidence, but its risk deeply impacts the quality of life of patients with food allergy and their families. Prevention of fatal food anaphylaxis must involve patients and their families, as well as the general public, public authorities, and patients’ associations.